IMPLEMENTASI GERAKAN LITERASI KITAB SUCI PADA MASA PANDEMI COVID-19 DI SMP NEGERI 3 MAGELANG - Asror, Chozin; Mu’anayah, Nur Alfi; Ifadah, Luluk (Jurnal Ilmiah Citra Ilmu, 2021)
Abstract This research began with the author's interest in the Bible Literacy Movement at SMP Negeri 3 Magelang. This study aims to describe the implementation of the Bible Literacy Movement during the Covid-19 Pandemic at SMP Negeri 3 Magelang and to find out the supporting and inhibiting factors. The method used is a descriptive qualitative research method. Data was collected by observation, interviews and documentation. The research subjects were principals, vice principals, PAI teachers and randomly selected students. In processing the data, the author uses the method of data reduction, data presentation, and verification. The results of the study show that: First, during the Covid-19 pandemic, the Bible Literacy Movement was carried out online and the implementation process included the stages of interpretation, organization, and application. While the implementation is carried out in 2 stages, namely the habituation stage and the development stage. Second, the factors that support the implementation of this activity are that students do not have dependence on one teacher, many students already have IT devices and can operate learning media, and the internet network is not too bad. While the inhibiting factors are the unpreparedness of students in participating in activities, the lack of educators who are ready to guide, and the absence of direct interaction between teachers and students. Keywords: Implementation, Qur’an Literacy Movement, Covid-19 pandemic.